Multiple Cranial Nerve Palsy & Choroid Tuberculoma in a Patient with Disseminated TB: A Clinic Biochemical Study - Parvaz, MH; Yesmin, S; Khalil, I; Rahman , MR; Uddin , AA (Bangladesh Journal of Medicine, 2023)
Disseminated Tuberculosis is a potentially lethal disease if not diagnosed and treated early. A high index of clinical suspicion and early diagnosis and timely institution of anti TB treatmen is life saving.Patient’s sociodemographic, clinical, labarotory investigations and treatment outcome were recorded in a case record form Here we report a case of 42 year old male, known case of diabetes mellitus, presented with the complaints of fever and headache for 1 month, dropping of both eyelids, diplopia and painful red eyes for 7 days. There was no sign of meningeal irritation. Neurological examination revealed proptosis and 3rd, 4th, 6th cranial nerve palsy as evident by bilateral ptosis, diplopia, restricted ocular movement in all direction. Fundoscopy showed choroid tubercle on left eye. CSF study suggestive of tubercular meningitis. CXR showed pleural effusion and pleural fluid study suggestive of tuberculous pleural effusion. We diagnosed him as disseminated tuberculosis (tubercular meningitis, ocular TB, pleural TB). After starting anti tubercular regimen and steroid, patient’s condition got improved. Disseminated tuberculosis usually presents with constitutional symptoms rather than respiratory features. Tubercular meningitis not always present with features of meningism. Choroid tubercle is pathognomic for tubercular meningitis. Early diagnosis and treatment can reduce the mortality, morbidity and complications of disseminated TB. J Medicine 2023; Vol. 34, No. 2(1) Supplement: 224